IMPLEMENTASI GOOGLE LOOKER STUDIO UNTUK VISUALISASI BENCANA ALAM DI INDONESIA. - Pasa Andita, Ageng (UNIVERSITAS STEKOM, 2026)
This study aims to visualize natural disaster data in Indonesia to identify patterns, distribution, and impact levels. The method used is the Extract, Transform, and Visualize (ETV) framework, utilizing Google Looker Studio as the primary tool for building an interactive dashboard. Data is sourced from the BNPB and BMKG open portals, which then undergoes cleaning, integration, and modeling processes. The analysis results reveal that although hydrometeorological disasters such as floods (29.9%) and extreme weather (25.3%) occur most frequently, geological disasters such as earthquakes and tsunamis cause the most casualties (34%) and injuries (46.4%). Geographically, densely populated areas such as West Java are the epicenters of disasters. The study concluded that Google Looker Studio is effective as a lightweight and collaborative business intelligence solution for disaster data visualization, thereby supporting data-driven decision-making in disaster risk mitigation and management in Indonesia.